Estudio de prefactibilidad para la instalación de una planta productora de hojuelas en base a kiwicha, quinua y cañihua fortificadas con hierro microencapsulado - Martinez Palet, Cristobal (2019)
The present study evaluates the commercial, technical, economic, financial and social viability of the installation of a flake-producing factory based on Andean cereals such as quinoa, kiwicha and cañihua and fortified with iron through microencapsulation: an innovation in the food industry that is gaining strength in recent years.